Associação da relação pescoço-coxa com a Síndrome Metabólica e seus componentes em universitários - Lisboa, Kenya Waléria de Siqueira Coelho (2018)
Chronic noncommunicable diseases (CNCDs), such as hypertension, diabetes mellitus (DM) and obesity stand out on the Brazilian agenda of health research priorities (ANPPS). Added to that context, the metabolic syndrome (MS) is a set of risk factors for cardiovascular diseases (CVDs). The use of anthropometric measures to investigate the metabolic syndrome has been assessed and disseminated worldwide, as these methods are easy to apply, low-cost, offer good predictability for many CNCDs and are accessible at the different health care levels. Little research has been done on the neck-to-thigh ratio (NTR), which is the ratio between the neck circumference (NC) and the thigh circumference (TC), although it is easy to measure. The objective of this study was to investigate the neck-to-thigh ratio (NTR) as an anthropometric index for identification of MS and its components in university students in Fortaleza, Ceará, Brazil. A quantitative and cross-sectional study was undertaken in a secondary database, which included 691 students from a public university. This research is part of the project funded by the Conselho Nacional de Desenvolvimento Científico e Tecnológico - CNPq, focused on the MS, which received approval from the Research Ethics Committee at Universidade Federal do Ceará (UFC) in accordance with protocol 208/2010. The data were analyzed using Statistical Package for the Social Sciences (SPSS) version 20.0. Descriptive analysis with central trend and dispersion, association (Chi-squared, Fisher’s Exact, Student’s t and Mann Whitney tests), correlation (Pearson) and the Receiver Operating Characteristic (ROC) curves were applied to identify the discriminatory power of NTR and the components of MS. Among the 691 college students, 62.2% were women, 94.1% single, the majority lived with their family (93.5%), 26.6% suffered from overweight and 70.5% of the participants were sedentary. The association between NTR and MS did not present a significant correlation in this study. The mean NTR was homogeneous between the students with and without MS. In the same sense, in the ROC curve, NTR did not reveal good discriminatory properties. Nevertheless, in the analysis of NTR with the MS components, positive correlations were found with two of these, blood pressure and triglycerides, as well as a negative correlation with High Density Lipoprotein (HDL-cholesterol), which means that the index can determine changes in these components. Thus, its practical use enables to determine the risk of development of change in SM components. In addition, studies in populations with different specificities need to be developed in order to clarify the use of RPCx as an anthropometric index, to be included in the criteria previously established by the competent organizations, to assist in the identification of MS.